Perancangan dan Implementasi Sistem Monitoring Suhu Ruang Server Berbasis IoT Menggunakan ESP32 dan Sensor DHT22 - Muhammad Reihan Daffa Putra; Rizky Ade Kusuma; Raymondus Trisaptono; Eka Puji Widiyanto (MDP Student Conference, 2026)
This study aims to design and implement an Internet of Things (IoT)-based server room temperature monitoring system capable of real-time monitoring, critical temperature notification, and automatic historical data logging. An experimental method was employed by implementing a system using an ESP32 microcontroller, a DHT22 sensor, and IoT platforms including Blynk and Google Spreadsheet for data visualization and storage. System testing was conducted in a server room environment with an average sampling interval of approximately 8 minutes. The results show that the system successfully records and transmits temperature data with a data transmission success rate above 99%. The measured temperature ranged from 19.5 to 25 °C and did not exceed the predefined alarm threshold. These results indicate that the proposed system operates reliably and can effectively support continuous server room temperature monitoring.